Batch study on the removal of mercury (II) ion from industrial wastewater using activated palm oil fuel ash - Kamaliah, Abdul Samad; Imla Syafiqah, Mohd Salleh; Mior Ahmad Khushairi, Mohd Zahari; Hafizuddin, Wan Yussof (Elsevier Ltd, 2019)
Palm oil fuel ash (POFA) was introduced as a raw material in this study to maximize the utilization of oil palm waste. Activated POFA was used as the adsorbent for the removal of mercury (II) ion from industrial wastewater. In this present work, a batch experimental work was conducted in order to study the capability of activated POFA for removal of mercury (II) ion from industrial wastewater. The evaluate was carried out at optimum condition of pH 2, contact time 5 h, agitation speed 150 rpm, adsorbent dosages 0.25 g, and initial mercury (II) ion concentration 5 mg/L. From this work, it was found that that activated POFA was a good adsorbent for mercury (II) ion removal with 91.18% mercury removal from industrial wastewater. This result was comparable to other researchers in the range from 90 to 95% mercury (II) ion removal. In contrast, only 60.41% mercury removal was recorded by raw POFA. Overall, activated POFA has the potential to be used as an adsorbent for the removal of mercury (II) ion from industrial wastewater due to its high performance and availability at low cost. The findings from this study can be used as references for future application in industrial wastewater treatment as well as other industries and activities such as gold mining, chemical industries and agriculture, which are related to mercury contamination in their industrial wastewater treatment plant.